Of mice, microglia, and (wo)men: a case series and mechanistic investigation of hydroxychloroquine for complex regional pain syndrome. (25th September 2020) - Haight, Elena S.; Johnson, Emily M.; Carroll, Ian R.; Tawfik, Vivianne L.
Abstract : We present a case series of patients treated with hydroxychloroquine for complex regional pain syndrome and demonstrated analgesia and reduced spinal cord autoinflammation in a preclinical model of complex regional pain syndrome. Abstract: Introduction: Complex regional pain syndrome (CRPS) is a condition that occurs after minor trauma characterized by sensory, trophic, and motor changes. Although preclinical studies have demonstrated that CRPS may be driven in part by autoinflammation, clinical use of immune-modulating drugs in CRPS is limited. Hydroxychloroquine (HCQ) is a disease-modifying antirheumatic drug used to treat malaria and autoimmune disorders that may provide benefit in CRPS. Objectives: To describe the use of HCQ in patients with refractory CRPS and investigate possible mechanisms of benefit in a mouse model of CRPS. Methods: We initiated HCQ therapy in 7 female patients with refractory CRPS undergoing treatment at the Stanford Pain Management Center. We subsequently undertook studies in the mouse tibial fracture–casting model of CRPS to identify mechanisms underlying symptom reduction. We evaluated behavior using mechanical allodynia and spinal cord autoinflammation by immunohistochemistry and enzyme-linked immunosorbent assay. Results: We treated 7 female patients with chronic, refractory CRPS with HCQ 200 mg twice daily for 2 months, followed by 200 mg daily thereafter. Two patients stopped HCQ secondary to lack of response or side effects. Overall, HCQ significantly improved average numerical rating scale pain from 6.8 ± 1.1 before HCQ to 3.8 ± 1.9 after HCQ treatment. In the tibial fracture–casting mouse model of CRPS, we observed reductions in allodynia, paw edema, and warmth following daily HCQ treatment starting at 3 weeks after injury. Spinal cord dorsal horn microglial activation and cytokine levels were also reduced by HCQ treatment. Conclusion: Together, these preclinical and clinical results suggest that HCQ may benefit patients with CRPS at least in part by modulating autoinflammation and support further investigation into the use of HCQ for CRPS.